ENHANCING STUDENTS’ ENGLISH SPEAKING ABILITY THROUGH VRCHAT GAME AS LEARNING MEDIA - Pramujiono Cahyadi; Daffa Indra Arya Wardhana; Wildan Isa Ansori; Rafika Rabba Farah (Universitas Teknokrat Indonesia, 2022)
Era 5.0 or Society 5.0 is a human-centered technology-based era that aims to create convenient and efficient living circumstances and provide further innovation in the life sustainability area. Era 5.0 is visualized as capable of creating a multinational society, whether in business, social, and educational environments. Thus, English should be noted as a crucial matter needed in communicating and takes part in living within era 5.0 in the future. The current research was conducted because of the limited exploration in the previous study that discusses online game VRChat as a learning medium to enhance students’ English speaking ability. Therefore, this paper aims to fill the gap by investigating and exposing the VRChat game’s value as a learning medium to improve students’ ability to speak English. Mixed method research was applied in the current study to analyze and ensure the VRChat game’s advantages for enhancing students’ speaking ability. Moreover, interviews and testing were used as the instrument in this research. A random sampling of four students who have done taking the FLSP (Foreign Learning for Specific Purposes) course as the current study’s subject. Additionally, the analysis was done using descriptive statistics and hierarchical charts using Nvivo 12 plus. This study showed the use of VRChat games as a learning medium increased students’ ability to speak English, specifically on their accuracy and fluency. This research implies that the VRChat game can support English teaching as the learning media, especially in speaking subjects.